2016
DOI: 10.1063/1.4954107
|View full text |Cite
|
Sign up to set email alerts
|

Response of EBT3 Gafchromic films exposed to high energy electrons

Abstract: Abstract. The optical density as a function of dose and the energy dependence of EBT3 Gafchromic films were determined using electron beams with energies from 6 to 22 MeV. The films were scanned and separated into RGB channels. The red channel optical density is independent of energy in a range of 2-10 Gy for dose in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Thus, the results show no energy dependence of EBT3 Gafchromic films for electron beams with energies between 4 and 12 MeV in the dose range between 0.25 and 30 Gy. Our study extends the results reported by Sipil€ a et al 18 and Molina et al 19 for the energy independence of EBT3 films to lower energy and to dose levels lower than 2 Gy and higher than 10 Gy. Similar to our conclusions, Arjomandy et al 9 found only a weak energy dependence for EBT2 films when comparing their dose responses for electron beams of 6 and 20 MeV energy and for doses between 0.4 and 10 Gy.…”
Section: A Energy Dependence Of Ebt3supporting
confidence: 91%
See 1 more Smart Citation
“…Thus, the results show no energy dependence of EBT3 Gafchromic films for electron beams with energies between 4 and 12 MeV in the dose range between 0.25 and 30 Gy. Our study extends the results reported by Sipil€ a et al 18 and Molina et al 19 for the energy independence of EBT3 films to lower energy and to dose levels lower than 2 Gy and higher than 10 Gy. Similar to our conclusions, Arjomandy et al 9 found only a weak energy dependence for EBT2 films when comparing their dose responses for electron beams of 6 and 20 MeV energy and for doses between 0.4 and 10 Gy.…”
Section: A Energy Dependence Of Ebt3supporting
confidence: 91%
“…Finally, Reinhardt et al observed a maximum difference of 6% between EBT3 calibration curves for photon and proton beams. The only investigations on the energy dependence of EBT3 for different megavoltage electron beams were conducted by Sipilä et al and by Molina et al In the first study, the difference in response of EBT3 between four electron beams with energies between 6 and 16 MeV was evaluated to be within 0.5% for a single dose level of 2 Gy. In the second one, beam energies between 6 and 22 MeV were used and no energy dependence was found for doses between 2 and 10 Gy.…”
Section: Introductionmentioning
confidence: 99%
“…Since the mean energy and the dose-rate vary with SSD, depth in medium and off axis distance, it was necessary to use an energy-and dose-rate-independent dosimeter to measure depth dose curves and beam profiles, which is the case of EBT3 Gafchromic films. 16,22,23 We observed a decrease in the beam penetration, thereby in the energy, when the dose-rate increased (E = 4.9 MeV in Flash and E = 6 MeV in Conv). Further measurements showed that the beam energy gradually changed from 4.9 to 6 MeV, when using parameter combinations resulting in intermediate dose-rates.…”
Section: D Beam Profiles and Depth Dose Curvesmentioning
confidence: 81%
“…Since the mean energy and the dose‐rate vary with SSD, depth in medium and off axis distance, it was necessary to use an energy‐ and dose‐rate‐independent dosimeter to measure depth dose curves and beam profiles, which is the case of EBT3 Gafchromic films …”
Section: Discussionmentioning
confidence: 99%